2021
DOI: 10.1186/s40360-021-00504-y
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing, biofilm production, and detection of carbapenemase genes in multidrug-resistant Acinetobacter baumannii isolated from different infection sites using ERIC-PCR in Hamadan, west of Iran

Abstract: Background Acinetobacter baumannii is an opportunistic pathogen that can cause several kinds of nosocomial infections. Increasing antibiotic resistance as well as identifying genetic diversity and factors associated with pathogenicity and prevalence of this bacterium is important. The aim of this study was the investigation of molecular typing, biofilm production, and detection of carbapenemase genes in multidrug-resistant Acinetobacter baumannii isolated from different infection sites using ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In this study, out of 110 tested CRAB isolates, 86.4% (n=95) were biofilm producers, among which 31 (32.6%) were week biofilm producers, 40 (42.1%) were moderate biofilm producers, and 24 (25.3%) were strong biofilm producers. Similar results were reported previously [47], but still disagreement present with other study that reported different percentages [48]. This variation might be attributed with the widespread prevalence of biofilm-encoding genes among A. baumannii strains, variations of the biofilm-formation assay principles, or environmental factors [49].…”
Section: Discussionsupporting
confidence: 80%
“…In this study, out of 110 tested CRAB isolates, 86.4% (n=95) were biofilm producers, among which 31 (32.6%) were week biofilm producers, 40 (42.1%) were moderate biofilm producers, and 24 (25.3%) were strong biofilm producers. Similar results were reported previously [47], but still disagreement present with other study that reported different percentages [48]. This variation might be attributed with the widespread prevalence of biofilm-encoding genes among A. baumannii strains, variations of the biofilm-formation assay principles, or environmental factors [49].…”
Section: Discussionsupporting
confidence: 80%
“…In terms of carbapenemase-encoding genes, bla VIM was detected in 18% of the isolates, resembling the findings of [32] but differing significantly from the studies conducted by [33][34][35]. Interestingly, bla SPM was found in 50% of the isolates, contradicting the findings of [34], where none of the tested isolates carried this gene.…”
Section: Discussioncontrasting
confidence: 59%
“…Among the PCR-based fingerprint techniques, ERIC-PCR is preferred as an economical, simple, and fast method used to identify and distinguish Acinetobacter species [16]. Therefore, it is important to control infections in hospitals and periodically monitor antimicrobial resistance patterns in different regions for infection control [17] In this study, the ERIC-PCR technique was used to see the genetic distribution of A. baumannii strains which cause common nosocomial infections. Overall, the findings of this study showed that the ERIC-PCR method is a viable method to reveal the genetic diversity of different A. baumannii strains.…”
Section: Eric-pcr Analysismentioning
confidence: 99%